2015
DOI: 10.1155/2015/649709
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Elicitation and Germination Conditions on Biological Activity of Wheat Sprouts

Abstract: The influence of elicitation, time, and temperature of germination on the biological activity of wheat sprouts was studied. The total phenolics content (TPC), antioxidant activity (AA), and microbiological purity of seeds of three wheat cultivars elicited withSaccharomyces cerevisiae(Y) andSalix daphnoidesbark extracts (W) and their mixture (1 : 1) germinated in different conditions were studied. The increase of germination time caused an increase the TPC and AA for all tested wheat cultivars. Germination temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 21 publications
2
23
0
2
Order By: Relevance
“…Our previous study showed that elicitation and modification of germination conditions strongly influenced the phytochemical profile and biological activity of wheat sprouts. In addition, the effectiveness of elicitation as a “green” biotechnology tool to improve nutraceutical potential (especially antioxidant activity) of wheat seedlings was confirmed (Dziki, Gawlik‐Dziki, Kordowska‐Wiater, et al, ; Świeca & Dziki, ). To improve the nutraceutical potential of wheat, we used natural elicitors: 0.1% (w/v) of Saccacharomyces cerevisiae (SC) solution, 0.1% (vol/vol) Salix daphnoides (SD) bark extract, and their combinations (SC/SD 1:1).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Our previous study showed that elicitation and modification of germination conditions strongly influenced the phytochemical profile and biological activity of wheat sprouts. In addition, the effectiveness of elicitation as a “green” biotechnology tool to improve nutraceutical potential (especially antioxidant activity) of wheat seedlings was confirmed (Dziki, Gawlik‐Dziki, Kordowska‐Wiater, et al, ; Świeca & Dziki, ). To improve the nutraceutical potential of wheat, we used natural elicitors: 0.1% (w/v) of Saccacharomyces cerevisiae (SC) solution, 0.1% (vol/vol) Salix daphnoides (SD) bark extract, and their combinations (SC/SD 1:1).…”
Section: Introductionmentioning
confidence: 92%
“…In addition, the nutraceutical potential of sprouted seeds can by enhanced by elicitation, which is one of the effective methods used to enhance secondary metabolite production in numerous plant systems (Baenas, García‐Viguera, & Moreno, ). So far, infusions of willow bark (a source of salicylic acid—plant hormone) are known to be effective inducers of antioxidant synthesis in broccoli and wheat seeds (Dziki, Gawlik‐Dziki, Kordowska‐Wiater, & Domań‐Pytka, ; Dziki, Gawlik‐Dziki, Różyło, & Miś, ; Gawlik‐Dziki, Świeca, Dziki, & Sugier, ). Our previous study showed that elicitation and modification of germination conditions strongly influenced the phytochemical profile and biological activity of wheat sprouts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, microorganism growth is doubled at a temperature increase of 10 K until the maximum temperature is reached at which microorganisms can survive. Dziki, Gawlik‐Dziki, Kordowska‐Wiater, and Doman‐Pytka () showed that the microorganism level was within an acceptable limit by sprouting processes lasting up to 4 days at 15 or 20°C. At higher temperatures or longer sprouting times the aerobic bacteria and mold growth were enhanced to unacceptable levels.…”
Section: Introductionmentioning
confidence: 99%